Drosophila Hook-Related Protein (Girdin) Is Essential for Sensory Dendrite Formation. Issue 4 (9th June 2015) - Ha, Andrew; Polyanovsky, Andrey; Avidor-Reiss, Tomer
Abstract: The dendrite of the sensory neuron is surrounded by support cells and is composed of two specialized compartments: the inner segment and the sensory cilium. How the sensory dendrite is formed and maintained is not well understood. Hook-related proteins (HkRP) like Girdin, DAPLE, and Gipie are actin-binding proteins, implicated in actin organization and in cell motility. Here, we show that the Drosophila melanogaster single member of the Hook-related protein family, Girdin, is essential for sensory dendrite formation and function. Mutations in girdin were identified during a screen for fly mutants with no mechanosensory function. Physiological, morphological, and ultrastructural studies of girdin mutant flies indicate that the mechanosensory neurons innervating external sensory organs (bristles) initially form a ciliated dendrite that degenerates shortly after, followed by the clustering of their cell bodies. Importantly, we observed that Girdin is expressed transiently during dendrite morphogenesis in three previously unidentified actin-based structures surrounding the inner segment tip and the sensory cilium. These actin structures are largely missing in girdin mutant. Defects in cilia are observed in other sensory organs such as those mediating olfaction and taste, suggesting that Girdin has a general role in forming sensory dendrites in Drosophila . These suggest that Girdin functions temporarily within the sensory organ and that this function is essential for the formation of the sensory dendrites via actin structures.